The Pre-Austronesian ‘Liangdao Man’ - Chen, Chung-yu. author. aut Link
XXIX, 203 p. 45 illus., 41 illus. in color.
Keywords: This book adopts a comprehensive approach, drawing from archaeology, physical anthropology, human genetics, linguistics, cultural anthropology, ethnology and ethnography, to explore the Austronesian link of ‘Liangdao Man,’ and the origins of Austronesian language groups. Due to their dating 2,300~1,500 years earlier than Austronesian-speaking peoples, these two individuals should be Pre-Austronesian or Proto-Austroasiatic. The Matsu archipelago is situated off Fuzhou City's estuary in Fujian Province. In 2011–2012, the author unearthed two human skeletons, ‘Liangdao Man 1’ and ‘Liangdao Man 2,’ aged 8,300 and 7,500 years, respectively, on Liangdao Island, one of these islands. DNA analysis revealed that haplogroups E and R9 were identified, linking them to Austronesians of Taiwan aborigines’ maternal lineage.